The Role of Social Entrepreneurs in Sri Lanka - Nimeshi, G.K.S.; Surangi, H.A.K.N.S. (Faculty of Commerce and Management Studies, University of Kelaniya., 2023)
In recent years, there has been a growing body of literature on social entrepreneurship, yet researchers in developing countries have not adequately explored this field. This qualitative study delves into the role of social entrepreneurs in Sri Lanka, examining how they operate and the factors influencing their choices. Grounded in social reality and aligned with social constructionist philosophy, the research engaged ten selected social entrepreneurs through interviews and applied thematic analysis to interpret the data. The findings reveal valuable insights into the strategies employed by social entrepreneurs in starting and managing their enterprises. Individual and social factors such as family background, experience, social networks, and religion significantly influence the decision to become a social entrepreneur. The study's developed model bridges subjective experiences of social entrepreneurs with existing literature, contributing to a deeper understanding of how social entrepreneurship is practiced and constructed.
Keywords: Social Entrepreneurship; Social Constructionism; Qualitative; Narrative